Utilization of Instagram Social Media as a Marketing Promotion Media for Coffee Shops in Bekasi (Study on Instagram Account @Janjiancoffee) - Aulia, Adinda Dwi Nurul; Hadita, Hadita (PT FORMOSA CENDEKIA GLOBAL, 2024)
Seeing the development of coffee shops which is currently increasingly rapid, it is a threat to other coffee shop business people in terms of determining marketing strategies. One form of marketing strategy that is currently being implemented by many coffee shop business people is using Instagram social media to reach a wider market. This research discusses the use of social media Instagram as a marketing promotion medium for coffee shops in Bekasi (Study on the Instagram account @janiancoffee). This research method uses a qualitative descriptive approach. This research uses primary data and secondary data. Based on the results of the research and discussion, there are efforts made by Promise Coffee to increase sales by utilizing Instagram accounts, namely: conducting consumer interactions, collaborations, and holding events. This proves an increase in sales of coffee appointment products.